Systems Engineering Demystified - Holt, Jon (Packt Publishing, 2021)
Get to grips with systems engineering life cycles, processes, and best practices and discover techniques to successfully develop complex systems Key Features Discover how to manage increased complexity and understand systems better via effective communication Adopt a proven model-based approach for systems engineering in your organization Apply proven techniques for requirements, design, validation and verification, and systems engineering management Book Description Systems engineering helps us to understand, specify, and develop complex systems, and is applied across a wide set of disciplines. As systems and their associated problems become increasingly complex in this evermore connected world, the need for more rigorous, demonstrable, and repeatable techniques also increases. Written by Professor Jon Holt - an internationally recognized systems engineering expert - this book provides a blend of technical and business aspects you need to understand in order to develop successful systems. You'll start with systems engineering basics and understand the complexity, communication, and different stakeholders' views of the system. The book then covers essential aspects of model-based systems engineering, systems, life cycles, and processes, along with techniques to develop systems. Moving on, you'll explore system models and visualization techniques, focusing on the SysML, and discover how solutions can be defined by developing effective system design, verification, and validation techniques. The book concludes by taking you through key management processes and systems engineering best practices and guidelines. By the end of this systems engineering book, you'll be able to confidently apply modern model-based systems engineering techniques to your own systems and projects. What you will learn Understand the three evils of systems engineering - complexity, ambiguous communication, and lack of understanding Realize successful systems using model-based systems engineering Understand the concept of life cycles and how they control the evolution of a system Explore processes and related concepts such as activities, stakeholders, and resources Discover how needs fit into the systems life cycle and which processes are relevant and how to comply with them Find out how design, verification, and validation fit into the life cycle and processes Who this book is for This book is for aspiring systems engineers, engineering managers, or anyone looking to apply ...